Notable catalytic activity of CuO nanoparticles derived from metal-organic frameworks for improving the hydrogen sorption properties of MgH2 - Shukla, Vivek; Yadav, Thakur Prasad (John Wiley & Sons Inc., 2022)
The present studies describe and discuss the application of the highly porous metal-organic framework (MOF-199) through its conversion into CuO nanoparticles. CuO nanoparticles produced from MOF-199, as well as their graphene templated counterpart ([CuO]@Gr), have been employed to improve the hydrogen sorption properties of the front-running hydride (MgH2). The MgH2-(CuO) and MgH2-(CuO)@Gr have been studied in terms of their hydrogen sorption properties. The onset desorption temperature for (CuO)@Gr catalyzed MgH2 has been found to be 229 degrees C, which is 121 degrees C and 12 degrees C lower than MgH2 and MgH2-(CuO). The MgH2-(CuO) sample absorbs hydrogen of 5.02 wt % in 1 minute, and 5.22 wt% in 5 minutes and desorbs 1.48 wt% in 5 minutes, and 5.55 wt% in 20 min at 290 degrees C. However, the MgH2-(CuO)@Gr sample absorbs hydrogen to the tune of 6.01 wt% in 1 minute and 6.22 wt% in 5 min and desorbs 2.32 wt% in 5 minutes and 6.01 wt% in 12 minutes at 290 degrees C. The activation energy of (CuO)@Gr catalyzed MgH2 has been found to be 82.83 kJ/mol, which is lower by 77.23 kJ/mol from BM MgH2. The change in desorption enthalpy for MgH2-(CuO) sample has been found to be 75.18 kJ/ mol and 68.34 kJ/mol for the MgH2-(CuO)@Gr sample, respectively. A remarkable impact of graphene addition is that the storage capacity hardly changes on cycling here and remains -6 wt% even after 10 cycles without any substantial deterioration. Repeated cycling further leads to the formation of Cu nanoparticles and prevents agglomeration during cycling. On the basis of X-Ray diffraction, transmission/scanning electron microscopic, RAMAN spectroscopy investigations, and Fourier transmission infrared spectroscopy, a plausible catalytic mechanism resulting from MOF-199 derived (CuO)@Gr catalyst on MgH2 has been discussed.